Glucagon-like peptide-1 receptor agonists as add-on therapy to basal insulin in patients with type 2 diabetes: a systematic review - Berlie H (Dove Medical Press, 2012)
Helen Berlie, Kathryn M Hurren, Nicole R PinelliEugene Applebaum College of Pharmacy and Health Sciences, Wayne State University, Detroit, MI, USAAbstract: The prevalence of obesity and diabetes continues to rise in the US. Glucagon-like peptide-1 receptor agonist (GLP-1RA) is an effective treatment option for type 2 diabetes mellitus (T2DM) that promotes weight loss. Common and effective treatment options added to metformin therapy (basal insulin, sulfonylureas, and pioglitazone) contribute to weight gain, which makes the addition of GLP-1RAs advantageous. Exenatide was the first agent in this class and has recently been approved for use in combination with insulin glargine by the US Food and Drug Administration and the European Medicines Agency. Until recently, there was a lack of data examining basal insulin combined with these agents. The main purpose of this article is to review the prospective interventional data on the safety and efficacy of GLP-1RAs (exenatide, liraglutide, albiglutide, lixisenatide) combined with basal insulin therapy in nonpregnant adults with T2DM. Databases searched were PubMed, Cochrane Central Register of Controlled Trials and the Database of Systematic Reviews (inception to January 2012). Abstracts presented at relevant diabetes and endocrine meetings from 2009 to 2011 were also reviewed, as were reference lists of identified publications. A total of five studies met the criteria and were included in the review. Data from these studies demonstrated that this combination therapy offers advantages for the treatment of diabetes, such as additional lowering of A1c without major risk for hypoglycemia, lower basal insulin requirements, decreased postprandial glucose levels (with or without fasting plasma glucose decreases), and weight loss, or at the very least, less weight gain. However, the gastrointestinal side effects and high cost of these agents may limit their use. This review demonstrates that adding a GLP-1RA to an existing basal insulin regimen is a reasonable treatment strategy in nonpregnant adult patients with T2DM.Keywords: exenatide, liraglutide, lixisenatide, GLP-1, type 2 diabetes